ANALISIS KEBUTUHAN AIR BERSIH DI DESA SAWAPUDO KECAMATAN SOROPIA KABUPATEN KONAWE - Salfin Adrian Syarif; Rini Sriyani; Fathur Rahman Rustan (PRODI D3 TEKNIK SIPIL, 2018)
Water is a very important need for followers of human life. Without water there will be no life on earth. The need for air by humans is endless, especially water that is suitable for household use such as: bathin, cooking, even the most important is to drink. Water demant in the district of Sawappudo Village is higher but cannot be mached by the development of existing clean water facilities. This situation is exacerbated by the reduced air condition due to a prolonged dry season.The research objective is to find out the debit (Q) needs of clean air in Sawapudo Village, Kec. Soropia Kab. Konawe in 2018-2023 which can be used to meet the clean water needs of the Sawapudo Village community, and projecting the population using Geometric methods.The results of the study were obtained water requirements in 2018 in Sawapudo Vollage which amounted to 0.789 liters / second and in 2023 the total demand for clean water in Sawapudo Village was 1,016 liters / second. When compared with the demand discharge in 2023 of 1,016 ltr / sec, with the intake pipe discharge of 2 liters / second, the source discharge (Q source)> discharge needs (Q requirement)